2006
DOI: 10.1007/s10544-006-9142-z
|View full text |Cite
|
Sign up to set email alerts
|

A low temperature bonding of quartz microfluidic chip for serum lipoproteins analysis

Abstract: A low-temperature bonding method for microfabrication of quartz microfluidic chips has been developed. The bonding process involved two steps: pre-bonding and post-annealing at low temperature. The bonding quality was evaluated by measuring the shear force at bonding interface and the electrical properties of the chips. Shear force of 5.66 MPa (566 N/cm(2)) was obtained in a bonded chip after a post-annealing at 200 degrees C for 6 h. We owe the strong bonding strength to the formation of Si-O-Si bonds at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 31 publications
(23 reference statements)
1
13
0
Order By: Relevance
“…Our finding that bare silicon has a stronger inhibitory effect on the polymerase than SiO 2 (RBI = 2.2 × 10 2 versus RBI = 4.4 × 10 2 without BSA) is in line with the literature [1,2,4]. Surprisingly, SiO 2 quartz (RBI = 2.9 × 10 3 ), which already has been used in microfluidics [39][40][41], does not have as strong of an effect as silicon or silicon with a 560 nm layer of SiO 2 . Because SiO 2 has at least 12 crystalline forms [42] which may be produced by both oxidation or chemical reaction deposition, its inhibition properties need further investigation.…”
Section: Materials Inhibitory Effectsupporting
confidence: 91%
“…Our finding that bare silicon has a stronger inhibitory effect on the polymerase than SiO 2 (RBI = 2.2 × 10 2 versus RBI = 4.4 × 10 2 without BSA) is in line with the literature [1,2,4]. Surprisingly, SiO 2 quartz (RBI = 2.9 × 10 3 ), which already has been used in microfluidics [39][40][41], does not have as strong of an effect as silicon or silicon with a 560 nm layer of SiO 2 . Because SiO 2 has at least 12 crystalline forms [42] which may be produced by both oxidation or chemical reaction deposition, its inhibition properties need further investigation.…”
Section: Materials Inhibitory Effectsupporting
confidence: 91%
“…Recently, we have demonstrated that a low-temperature bonding of quartz microfluidic chips for serum lipoproteins analysis [1], LDL and HDL lipoproteins in the serum were separated by using Tricine buffer with methylglucamine. We observed that the analysis of blood samples with microfluidic devices was difficult due to surface adsorption of blood components which resulted in adsorption of sample on the walls leading to change the surface properties of the microchannels.…”
Section: Introductionmentioning
confidence: 99%
“…Following LIF detection, lamp-based approaches form the second largest group of optical detection techniques used for microchip separations. Several examples of lamp-based excitation using epifluorescence microscopes combined with photomultiplier tube (PMT) detection have been reported [79,124,125], from the high speed separation of trypsin inhibitor and BSA [80,124] to the separation of lowdensity and high-density lipoproteins [126] in the serum.…”
Section: Lamp-based Fluorescence Detectionmentioning
confidence: 99%
“…A low-temperature bonding method for microfabrication of quartz chips without the need for clean room conditions, and intermediate layer has been developed [126]. The reliability and performance of the fabricated chip were demonstrated through a complete separation of serum lipoproteins by CZE-LIF.…”
Section: Proteins From Biological Fluidsmentioning
confidence: 99%